Freight Management System: Logistic II: Vendor Portal, Audit Management, Vehicle Reservation System, Fleet Management, and Document Tracking System (Approval): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
These projects consist of various submodules that factor the whole EIS. Freight ManagementSystem; Logistic II: Vendor Portal, Audit Management, Fleet Management, VehicleReservation, and Document Tracking System (Approval) is a project that enables the logisticsprocess to be easier and more convenient. Other sub-models of other subsystems will bementioned and also create an impact on the process of this project. That's why we developedthis system to give more functionality, security, and effectiveness to the client.The researchers found out that the system is accurate and efficient. The technical function ofthe system is currently functioning according to the expected outcome. The system currentlyis able to run 24/7 owing to the fact that of the cloud server. Also, it currently exists as time-saving due to the fact that a cloud server serves the work.Being part of the subsystem has met the standard. The team successfully completed the taskaccording to everyone's given task. The integration of the whole EIS depends on each of itssubsystems. Dysfunction of one subsystem may lead to disorganization of the whole system.Changes and adjustments can occur depending on the client's requirements.
Keywords: IT & Management